Pemetaan Potensi Lokasi Pengungsian Akibat Bencana Letusan Gunung Agung di Kabupaten Karangasem Berbasis Sistem Informasi Geografis (SIG) - IRAWAN, I GEDE ADHI; DIARA, I WAYAN; BHAYUNAGIRI, IDA BAGUS PUTU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
The Mapping Potential Location of Evacuation Due to the Mount Agung Eruption Disaster in Karangasem Regency Based on Geographic Information  System (GIS) The eruption of Mount Agung was a disaster for people in Karangasem  Regency. The volcanic eruption caused loss of life. One of the countermeasures was he provision of location point for evacuation based on geographic information ystem and the construction of WebGIS with the ArcGIS Online program so that it can be accessed by people easily. This research was done in December 2018 until April 2019. The methods were used field survey and scoring method that utilizing patial data. The survey was done outside of the disaster-prone area in Karangasem Regency and dangerous radius 6, 9 and 12 km based on Mount Agung disaster area map, the Province of Bali such as school, balai banjar and sport field. School, balai banjar and sport field have the potential to become refugee camps. The School has he high and medium potential classes that are 102 and 92 places. Balai banjar has high, medium and low potential classes that are 126, 101 and 20 places. Sport field has medium and low potential classes that are 1 and 6 each places. The information ystem of potential refugee locations in Karangasem Regency based on WebGIS can provide information to the government and the community so that it can reduce the mpact caused by the disaster of Mount Agung. The WebGIS that can be accessed is: https://gunungagung.maps.arcgis.com/home/index.html.